Chinese foreign policy toward Sudan: reality and future - Ali, Selim Katia (The International and Political Journal, 2022)
In its foreign policy towards different regions of the world, China relied on employing a soft power strategy, depending on economic and trade power and foreign investment in order to enhance its influence and expansion in these regions, and in line with its ambition to emerge as a global power that cannot be bypassed in regional and international interactions. Towards the continent of Africa is a practical embodiment of this policy. Sudan, with its economic and geographic capabilities and capabilities, has been a target of Chinese policy with the aim of strengthening its political and economic presence in this important country. The Chinese policy towards Sudan is not superior to China’s comprehensive strategy, which seeks to have a regional and international role in various aspects of international relations, which indicates China’s desire to shift the international system from unipolarity, which embodies the hegemony of the United States, albeit relatively, to a multipolar system , particularly in the economic aspects.